Migration in Prague and the Prague Metropolitan Area - Šašek, Miloslav (Migracja w Pradze i praskim obszarze metropolitalnym, 2010)
The text is focused on migration in the Czech Republic in the time of transformation of Czech society after 1989. Suburbanization tendencies have been on the rise since the mid 1990s in the Czech Republic. The analysis of migration shows hierarchical relations and the strengthening of a dominant position of Prague and the whole area of central Bohemia inthe settlement system of the Czech Republic. The process of concentration in the metropolitan areas will continue with the dominating area in central Bohemia.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 110, s. 125-137